Economic Growth in Indonesian New Outonomous: Social-Economic Perspective - Rochmatullah, Mahameru Rosy; Winarna, Jaka; Gantyowati, Evi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
This study explores the Indonesian economic growth in the new autonomous regions using social - economy perspective. More specifically, social - economic issues are proxied on population, poverty rates, education levels, local tax revenues, and distribution of local government social assistance. Meanwhile, community economic growth is proxied by GRDP per capita (PE). The Indonesian economic growth and social-economy issues are measured using Ordinary Least Square (OLS). This study uses new autonomous regions data in Indonesia formed in 2003 – 2008. Employing multiple linear regression, the test results revealed that variable of local tax revenue (PD) was consistently able to explain PE. The same results are shown in the robustness test, where researchers predict the economic growth of the community with the Human Development Index (HDI). In the discussion section, community economic growth represented by PE continues to increase along with the increase in PD and HDI. The conclusion in this study is community economic growth increased since 2009, marked by an increase in PD along with HDI. As an implication, researchers suggest that practitioners and academics use local taxes to measure the community economy in new autonomous regions in Indonesia.